Housing and macroprudential policy - Muellbauer, J (University of Oxford, 2024)
Housing has been heavily implicated in many financial crises, e.g. in the Global Financial Crisis of 2008-9. Since the GFC, new macroprudential frameworks have been introduced across the globe, with housing-related tools prominent. This paper explains how the housing-related financial accelerator operates, and discusses institutional differences affecting the transmission and amplification of house price and credit shocks and therefore risks to the financial system and to the resilience of households. The objectives of housing-related macroprudential policy are discussed and research on diagnosing potential housing risk critically reviewed. Limitations of the literature on the effectiveness of housing-related macroprudential tools in international panel studies are examined, including from the neglect of country-heterogeneity, except in fixed effects. How aggregate cost-benefit analyses of the consequences of macroprudential policies has benefitted from the development of the Growth-at-Risk framework is explained. Research is reviewed on the distributional implications, often negative in the short-run, for example, on access to credit of lower income and first-time buyer households, but beneficial in the longer run. The importance of a general equilibrium approach integrating micro and macro data is emphasised, and developments in the agent-based modelling approach are discussed. The need to coordinate macroprudential policies with other housing-related policies is highlighted.